Numerical Analysis Of Swirl Intensity In Turbulent Swirling Pipe Flows - Tamrin, K. F.; Nadeem Ahmed, Sheikh; Rahmatullah, B. (UTM Press, 2016)
Swirling flows are often observed in nature such as weather systems, cyclones and tornados. A number of applications use swirling nature of flow for enhanced mixing, heat transport and other transport phenomena. Naturally occurring swirls as well as induced swirls are often usually turbulent in nature. Understanding the flow physics of turbulent swirling flow is important for better understanding and control of processes involving swirling flows. With the increase of computational resources and advancements in turbulent flow modelling, it is now possible to simulate highly complex flow structures. Here turbulent swirling flow induced by guide vanes is studied using Computational Fluid Dynamics (CFD) simulations in a two-dimensional axisymmetric channel. The results for the variation of velocity components are compared with the work of an earlier research. The results are initially compared for the evaluation of best discretisation scheme. It was observed that the second-order and third-order schemes produced similar results. To simulate the turbulent flow two equations (k-ε) model and the five equations Reynolds Stress Model (RSM) are used. The comparison of both models with higher order discretisation schemes shows that the standard k-ε model is incapable of predicting the main features of the flow whilst RSM yields result close to the experimental data.